Political Communication Experiences of Sundanese Muslim Women Politicians - Dewi, Evie Ariadne Shinta; Shalisa, Alina (Political Science Program, Universitas Negeri Semarang, 2020)
ThisÂ researchÂ aimedÂ toÂ understand the political communication ofÂ Sundanese Muslim Women Politicians in West JavaÂ in interactingÂ with their partnersÂ in political parties and their constituents.Â By using a qualitative research method with a case study approach involving five informants who were selected purposively based on predetermined characteristics, theÂ data collection techniqueÂ usedÂ literature review, in-depth interviews,Â and non-participant observation. The results showed that: a) education from parents; b) the role of religious groups; c) the desire to overcome the problems that exist in society are the reasons for Sundanese Muslim Women Politicians to join political parties. In addition, their aim to become politicians is to become a mediator of communication between the community and the legislature and furthermoreÂ toÂ be able to play an activeÂ role in making pro-women policies. The novelty of this research is that Sundanese Muslim women position themselves as subordinate, not to be ordinate.Â Another result ofÂ theÂ researchÂ showedÂ the motives. ThereÂ areÂ twoÂ motives of Sundanese Muslim women politicians involved in politics, namelyÂ the â€œbecause ofâ€Â motiveÂ andÂ the â€œIn order toâ€ motive. The political communication ofÂ Sundanese Muslim Women PoliticiansÂ in West Java, especially when interacting with political party colleagues is interpreted as a process of building interpersonal relations. While political communication when interacting with constituentsÂ is interpreted as communication to build sympathy and support.